Clinical and Epidemiologic Features of Cryptosporidium-Associated Diarrheal Disease Among Young Children Living in Sub-Saharan Africa: The Vaccine Impact on Diarrhea in Africa (VIDA) Study. (19th April 2023) - Hossain, M Jahangir; Powell, Helen; Sow, Samba O; Omore, Richard; Roose, Anna; Jones, Joquina Chiquita M; Zaman, Syed M A; Badji, Henry; Sarwar, Golam; Kasumba, Irene N; Onwuchekwa, Uma; Doh, Sanogo; et al.
Abstract: Background: As part of the Vaccine Impact on Diarrhea in Africa (VIDA) Study, we examined the prevalence, clinical presentation, and seasonality of Cryptosporidium in children to understand its relative burden after the introduction of rotavirus vaccine. Methods: VIDA was a 3-year, age-stratified, matched case-control study of medically attended acute moderate-to-severe diarrhea (MSD) in children aged 0–59 months residing in censused populations at sites in Kenya, Mali, and The Gambia. Clinical and epidemiologic data were collected at enrollment, and a stool sample was tested for enteropathogens by quantitative PCR. An algorithm was created based on the organism's cycle threshold (Ct) and association with MSD to identify the subset of Cryptosporidium PCR-positive (Ct <35) cases most likely to be attributed to MSD. Clinical outcomes were assessed at 2–3 months after enrollment. Results: One thousand one hundred six (22.9%) cases of MSD and 873 controls (18.1%) were PCR positive for Cryptosporidium ; 465 cases (42.0%) were considered attributable to Cryptosporidium, mostly among children 6–23 months. Cryptosporidium infections peaked in The Gambia and Mali during the rainy season, while in Kenya they did not have clear seasonality. Compared with cases with watery MSD who had a negative PCR for Cryptosporidium, cases with watery MSD attributed to Cryptosporidium were less frequently dehydrated but appeared more severely ill using a modified Vesikari scale (38.1% vs 27.0%; P < 0.001), likely due to higher rates of hospitalization and intravenous fluid administration, higher prevalence of being wasted or very thin very thin (23.4% vs 14.7%; P < 0.001), and having severe acute malnutrition (midupper arm circumference <115 mm, 7.7% vs 2.5%; P < 0.001). On follow-up, Cryptosporidium -attributed cases had more prolonged and persistent episodes (43.2% vs 32.7%; P <0 .001) and linear growth faltering (change in height-for-age z score between enrollment and follow-up: −0.29 vs −0.17; P < 0.001). Conclusions: The burden of Cryptosporidium remains high among young children in sub-Saharan Africa. Its propensity to cause illness and further impact children longer term by compromising nutritional status early in life calls for special attention to enable appropriate management of clinical and nutritional consequences. Abstract : The burden of Cryptosporidium remains high among young children in sub-Saharan Africa. Its propensity to cause illness and further impact children longer term by compromising nutritional status early in life necessitates appropriate management of clinical and nutritional consequences.